THE SPECIFICITY OF NON - VERBAL COMMUNICATION OF A TECHNOLOGY TEACHER - Henryk, NOGA (Trends in education, 2010)
The article was meant to show the results of research conducted among teachers who point out that non-verbal communication is a very important element of educating children. It has turned out that the correct interpretation of non-verbal messages which are sent from teachers to pupils the latter one can remember the new material quicker and easier. Most of the respondents have claimed that they pay attention to their posture, gestures and face expressions during their lessons and by this they try to make it easier for their pupils to get familiar with new pieces of knowledge.
Keywords: technology teaching; interpersonal communication